Mendeteksi Kecurangan Laporan Keuangan Dengan Analisis Fraud Diamond Dalam Perspektif Islam (Studi Empiris Bank Umum Syariah di Indonesia) - Hendra Galuh Febrianto; Amalia Indah Fitriana (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
As a Sharia-based financial intermediary, sharia commercial banks operate based on sharia principles (Islam), and procedures are based on the provisions of the Koran and Hadith. Financial statements in Islamic bank accounting are financial statements that describe the functions of Islamic banks. But the banking sector is the sector that has the most fraud/fraud cases compared to other sectors. Fraud of financial statements is considered a risk because it does not carry out a mandate which causes financial statements to be inaccurate and violate Sharia principles. The purpose of this study is to detect fraudulent financial statements by analyzing diamond fraud in Islamic perspectives through financial stability, effective monitoring, rationalization, and capability with the ultimate goal of recommending policies to improve Sharia banking management following sharia principles. This type of research uses explanatory research with a quantitative approach. Analysis of the data in the study used multiple linear regression analysis on the financial statements of 12 Islamic banks in Indonesia from 2013 to 2017. The results of this study's Financial Stability, Effective Monitoring, and Capability variables did not affect Financial Report Fraud. While the Rationalization variable affects the Fraud of Financial Statements.